Improving the clinical understanding and measurement of dissociation - Cernis, E (2017)
'Dissociation' describes a range of anomalous perceptual, cognitive and affective experiences that occur transdiagnostically. Examples include mental blanks, and feeling 'unreal'. Whilst its ubiquity is becoming accepted by clinicians, there is currently little understanding of the mechanistic role played by dissociation in clinically important presentations. The present thesis addresses this gap in two ways: by establishing the role dissociation plays in a key clinical presentation (youth deliberate self-harm; [DSH]), and by offering an updated measure of dissociation for use in future research. In Paper A, a review of nineteen eligible studies found an association between deliberate self-harm and dissociation, with more severe dissociation associated with more severe DSH, DSH in more locations on the body, and use of multiple methods of DSH. However, the review was unable to conclusively determine the direction of the association, largely due to limitations in studies' research designs. In Paper B, the development and psychometric properties of a new, clinically useful and up-to-date measure of dissociation are described. Clinician and service user consultation were used in the early stages to ensure a comprehensive representation of dissociative experiences. The result is a measure with five subscales with good validity and reliability. Suggestions for further validation of the measure are also made.